Comparative Thermal Analysis of Turboprop and Turbofan Engines Ideal Brayton Cycle Efficiency and Performance Implications - Cahya Wahyu Pribadi, Elwas; Abdul Ghofur,; Rachmat Subagyo,; Mastiadi Tamjidillah,; Aqli Mursadin,; Ma’ruf, (International Journal of Marine Engineering Innovation and Research, 2026)
Comparative thermal analysis of turboprop and turbofan engines in aircraft propulsion systems, with a focus on ideal thermal efficiency based on the Brayton cycle. Thermal efficiency, a dimensionless parameter representing the ratio of heat converted into useful work to the total heat input, is a fundamental indicator of engine performance and energy utilization. Turboprop engines, such as the Garret TPE331-10 powering the CASA C-212 Aviocar, operate as hybrid systems generating both jet thrust and shaft power for propeller rotation. In contrast, turbofan engines, exemplified by the CFM56-3CI, utilize a large bypass fan to achieve higher mass airflow and improved thrust efficiency at subsonic cruise conditions. This study quantitatively evaluates and compares the ideal thermal efficiencies of both engine types using data from previous studies. The analysis reveals that the CFM56-3 turbofan achieves an ideal thermal efficiency of approximately 70.51%, significantly higher than the TPE331-10 turboprop's 48.99%. This 21.52 percentage point difference is primarily attributed to the turbofan's higher compressor pressure ratio, enabling more effective energy conversion within the Brayton cycle. However, the paper also discusses the trade-off between thermal efficiency and propulsive efficiency, noting that turboprops excel at low to medium speeds due to superior propulsive efficiency from their propellers. The findings underscore that while turbofans are better suited for high-speed, long-range flights, turboprops remain optimal for short-haul operations. This comparison provides valuable insights for engineers, designers, and operators in selecting appropriate propulsion technologies and optimizing energy use across various flight missions.